Integration of Religious Education and Morality in Early Childhood to Build a Foundation of Faith and Piety - Saputri, Dwi Wahyu Ro'is; Zainuddin, Muhammad; Pramono, Pramono (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2026)
Early Childhood Education (ECE) is a crucial stage in providing educational stimulation for children aged 0–6 years, particularly during the golden age, which plays a significant role in character formation. In the era of globalization and digitalization, children face various moral challenges, making the integration of religious and moral values an urgent necessity in ECE learning. Values such as honesty, responsibility, compassion, and tolerance serve as a fundamental basis for shaping children’s character to become faithful and pious individuals. The internalization of religious and moral values requires collaboration among teachers, parents, and the social environment to ensure consistency and sustainability in children’s education. This study aims to describe the integration of religious and moral values in early childhood education as an effort to form characters of faith and piety at TK Al Hidayah Sawentar 04. The research employed a qualitative approach using a case study method. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The findings indicate that religious and moral values are integrated through daily prayer routines, teachers’ exemplary behavior, and the use of Islamic learning media such as illustrated stories and religious children’s songs. This integration positively influences children’s behavior, including politeness, honesty, and care for others. The study concludes that integrating religious values in ECE plays a strategic role in developing children’s spiritual character and may serve as a reference for other ECE institutions.